Evaluasi Suhu dan Kelembapan Udara terhadap Produktivitas Padi dan Ubi Kayu di Kabupaten Serdang Bedagai - Dela Arinda; M. Izhar; Annida Fauziyyatul Afifi; Safrizal Safrizal (Biocaster : Jurnal Kajian Biologi, 2026)
Changes in climate elements such as air temperature and humidity have the potential to affect food crop productivity. This study aims to analyze the relationship and influence of average temperature, maximum temperature, minimum temperature, and air humidity on rice and cassava productivity in Serdang Bedagai Regency for the period 2014–2023. Productivity data were obtained from the Central Statistics Agency (BPS), while temperature and dew point data came from ERA5 developed by the European Centre for Medium-Range Weather Forecasts (ECMRWF). Air humidity was calculated using the Magnus–Tetens equation. The analysis was carried out using correlation and multiple linear regression. The results showed that the relationship between climate factors and crop productivity tended to be weak to moderate. In rice, minimum air temperature had a moderate negative correlation (r = -0.54), while humidity had a fairly strong positive correlation (r = 0.68). In cassava, minimum air temperature had a weak negative correlation (r = -0.32), while humidity had a moderate positive correlation (r = 0.55). The regression results indicate that climate factors simultaneously had no significant effect on rice productivity (p = 0.573; R² = 0.39) or cassava (p = 0.483; R² = 0.446). This finding suggests that air temperature and humidity make limited contributions and have not yet demonstrated a statistically significant effect on crop productivity in Serdang Bedagai Regency.